Complex treatment of hoof of cows for ungulomycosis - N. M. Khomyn; V. V. Pritsak; I. I. Ihlitskyi; S. V. Tsisinska (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Under modern conditions of cattle breeding, ungulates are often exposed to various adverse factors associated with errors in feeding, maintenance, and corrective cleaning during the winter-stalling period. The hooves of cows, which are often exposed to multiple adverse factors, lead, for the most part, to the development of inflammatory processes in the area of the base of the skin of the sole, sometimes to septic genesis, complicated by keratomycetes. As is known, the purulent inflammatory process in this part of the hoof contributes to a decrease in the productivity of cows, which leads to significant economic losses. Treatment methods used for ungulomycosis do not always give the desired effect. Therefore, the work aimed to develop an effective method of treating cows with ungulomycosis using medicinal substances with antibacterial, antifungal, stimulating, and regenerative action. For research, two groups of cows with 5 animals each were formed, selected according to the principle of analogs regarding the nature and location of the pathological process. For therapeutic purposes, cows of both groups underwent orthopedic cleaning, irrigation of the surface of the soles of the hooves with a 0.02 % furacilin solution. A finely grated (separately) mixture of potassium permanganate boric acid and syntomycin liniment was applied to the affected area of the animals of the control group, and povidone-iodine 10 % in combination with a 30 % dimexide solution was applied to the surface of the hoof (corolla and sole area) of the experimental group after novocaine blockade, diluted with a 0.5 % solution of novocaine and, subsequently, levomekol ointment; carried out ultraviolet irradiation of cows with a PRK-2 lamp at a dose of 250 mer/hour/m2 for 25 min. three times a week, and 10 ml of trivit was administered intramuscularly three times a week. Animals of both groups were given antiseptic bandages and orthopedic shoes on their hooves. Clinical, biochemical, biophysical, immunological, bacteriological, mycological, and statistical studies were conducted. The proposed method of treatment improves the quality of the hoof horn, ensures the restoration of its structure, contributes to the elimination of defects, and shortens the duration of treatment by 10 days, which is confirmed by the results of the research conducted.